Les traités entre le Fuuta-Tooro et Saint-Louis : commerce, taxes et sécurité à l’intersection (1785-1808) - Cheikh Sene (Afriques)
Between the official end of the first English occupation of Senegal in 1783 (Treaty of Versailles) and the second English occupation of St. Louis in 1809, France concluded only three treaties with the Fuuta-Tooro, aiming to revive trade, ensure the security of its merchants, and resolve issues related to customs and taxes. In 1776, Fuuta-Tooro underwent a Theocratic Revolution, rejecting the authority of Saint-Louis in order to uphold one of the revolution’s core principles: combating the slave trade while continuing to collect taxes. The sovereignty of Fuuta-Tooro clashed with the pressures of French authority in Saint-Louis, which sought to conduct its commercial activities in the region freely. The three treaties signed in 1785, 1802, and 1806 between France and Fuuta-Tooro were all similar in nature, and each ultimately failed as both parties sought to protect their own interests.